2019
DOI: 10.1002/glia.23723
|View full text |Cite
|
Sign up to set email alerts
|

The voltage‐gated calcium channel CaV1.2 promotes adult oligodendrocyte progenitor cell survival in the mouse corpus callosum but not motor cortex

Abstract: Throughout life, oligodendrocyte progenitor cells (OPCs) proliferate and differentiate into myelinating oligodendrocytes. OPCs express cell surface receptors and channels that allow them to detect and respond to neuronal activity, including voltage‐gated calcium channel (VGCC)s. The major L‐type VGCC expressed by developmental OPCs, CaV1.2, regulates their differentiation. However, it is unclear whether CaV1.2 similarly influences OPC behavior in the healthy adult central nervous system (CNS). To examine the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 66 publications
(140 reference statements)
0
24
0
Order By: Relevance
“…Please note that two distinct Pdgfrα-CreER transgenic mouse lines were used in this study: the Pdgfrα-CreER TM transgenic mouse line (Kang et al, 2010) was used for the majority of experiments and the lower efficiency (LE) Pdgfrα-CreER T 2 transgenic mouse line (Rivers et al, 2008), was used to perform the Tau-mGFP lineage tracing experiments, as we have previously demonstrated that the Pdgfrα-CreER TM transgenic mouse line cannot be used to induce OPC-specific recombination of the Tau-mGFP reporter, despite achieving the OPC-specific recombination of other transgenes (Pitman et al, 2019).…”
Section: Transgenic Mice and Their Housingmentioning
confidence: 99%
See 3 more Smart Citations
“…Please note that two distinct Pdgfrα-CreER transgenic mouse lines were used in this study: the Pdgfrα-CreER TM transgenic mouse line (Kang et al, 2010) was used for the majority of experiments and the lower efficiency (LE) Pdgfrα-CreER T 2 transgenic mouse line (Rivers et al, 2008), was used to perform the Tau-mGFP lineage tracing experiments, as we have previously demonstrated that the Pdgfrα-CreER TM transgenic mouse line cannot be used to induce OPC-specific recombination of the Tau-mGFP reporter, despite achieving the OPC-specific recombination of other transgenes (Pitman et al, 2019).…”
Section: Transgenic Mice and Their Housingmentioning
confidence: 99%
“…Acute coronal brain slices (300 µm) were generated from adult mice carrying the Pdgfrα-histGFP transgene using a VT1200s vibratome (Leica) as previously described (Pitman et al, 2019). Brain slices were transferred to a bath constantly perfused (2 ml/min) with ∼21 • C artificial cerebral spinal fluid (ASCF) containing: 119 mM NaCl, 1.6 mM KCl, 1 mM NaH 2 PO 4 , 26.2 mM NaHCO 3 , 1.4 mM MgCl 2 , 2.4 mM CaCl 2 , and 11 mM glucose (300 ± 5 mOsm/kg), saturated with 95% O 2 /5% CO 2, Whole cell patch clamp recordings of GFP + cells in the motor cortex were collected using a HEKA Patch Clamp EPC800 amplifier and pCLAMP 10.5 software (Molecular devices; RRID: SCR_011323).…”
Section: Whole Cell Patch Clamp Electrophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Their main purpose is the formation of the myelin sheath [4,5], which is complex and requires different stimuli. The influx of calcium is important for the maturation of oligodendrocyte precursor cells (OPC) and the induction of myelination [6][7][8]. Additionally, the local calcium concentration seems to be essential for myelin elongation and sheath development [9][10][11].…”
Section: Role Of Calcium Under Physiological Conditionsmentioning
confidence: 99%